Entomopathogenic nematodes for the control of phorid and sciarid flies in mushroom crops - Navarro, María Jesús; Gea, Francisco José (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the efficacy of two nematodes, Steinernema feltiae and S. carpocapsae, to control mushroom flies and to evaluate the effect of these treatments on Agaricus bisporus production. Two mushroom cultivation trials were carried out in controlled conditions, in substrate previously infested with the diptera Megaselia halterata and Lycoriella auripila, with two treatments: 106 infective juveniles (IJ) per square meter of S. feltiae and 0.5x106 IJ m‑2 S. feltiae + 0.5x106 IJ m‑2 S. carpocapsae. Another experiment was carried out using the same treatments to evaluate the possible nematode effect on mushroom yield. The number of adults emerging from the substrate was evaluated for each fly species. No decrease in the population of M. halterata was detected with nematode application, whereas the number of L. auripila was reduced in both treatments, particularly in the individual treatment with S. feltiae. The application of entomopathogenic nematodes has no adverse effect on mushroom production.